Job Strain and Late-Life Cognition: Findings From the Puerto Rican Elderly Health Conditions Study - Vigoureux, Taylor F D; Nelson, Monica E; Andel, Ross; Small, Brent J; Dávila-Roman, Ana Luisa; Crowe, Michael (Journal of aging and health, 2021)
Objectives: We examined associations between job strain and cognitive aging in a sample of older Puerto Ricans. Methods: Members of the Puerto Rican Elderly: Health Conditions study, aged 60-100 years at baseline, participated. Job strain indicators were quantified from O*NET (n = 1632) and a matrix of Job Content Questionnaire scores (JCQ; n = 1467). Global cognition was assessed twice across 4 years. Results: Controlling for age, sex, depressive symptoms, financial problems, hypertension, diabetes, childhood economic hardship, low job control and high job strain were consistently associated with greater cognitive decline. Adding education attenuated these associations. High education strengthened the JCQ job control-cognitive change link. Discussion: Low job control and high job strain may accelerate cognitive aging in this population. However, it may be more difficult to disentangle the intersecting roles of education and job strain in cognitive aging among older Puerto Ricans relative to older adults from contiguous United States or Europe.
Keywords: kognitivní dysfunkce; Cognition; United States; Hispanic or Latino; Portoriko; Hispánci a Latinoameričané; kognice; Cognitive Aging; Child; Humans; lidé; senioři; Cognitive Dysfunction; Spojené státy americké; dítě; Aged; Puerto Rico; kognitivní stárnutí